Digit forces bias sensorimotor transformations underlying control of fingertip position - Shibata, Daisuke; Kappers, Astrid M. L.; Santello, Marco (Frontiers in Human Neuroscience, 2014)
Humans are able to modulate digit forces as a function of position despite changes in digit placement that might occur from trial to trial or when changing grip type for object manipulation. Although this phenomenon is likely to rely on sensing the position of the digits relative to each other and the object, the underlying mechanisms remain unclear. To address this question, we asked subjects (n = 30) to match perceived vertical distance between the center of pressure (CoP) of the thumb and index finger pads (dy) of the right hand (“reference” hand) using the same hand (“test” hand). The digits of reference hand were passively placed collinearly (dy = 0 mm). Subjects were then asked to exert different combinations of normal and tangential digit forces (Fn and Ftan, respectively) using the reference hand and then match the memorized dy using the test hand. The reference hand exerted Ftan of thumb and index finger in either same or opposite direction. We hypothesized that, when the tangential forces of the digits are produced in opposite directions, matching error (1) would be biased toward the directions of the tangential forces, and (2) would be greater when the remembered relative contact points are matched with negligible digit force production. For the test hand, digit forces were either negligible (0.5-1 N, 0 ± 0.25 N; Experiment 1) or the same as those exerted by the reference hand (Experiment 2). Matching error was biased towards the direction of digit tangential forces: thumb CoP was placed higher than the index finger CoP when thumb and index finger Ftan were directed upward and downward, respectively, and vice versa (p < 0.001). However, matching error was not dependent on whether the reference and test hand exerted similar or different forces. We propose that the expected sensory consequence of motor commands for tangential forces in opposite directions overrides estimation of fingertip position through haptic sensory feedback.